Optic Disc Neovascularization in Tubercular Serpiginous-Like Choroiditis. (18th May 2020) - Bansal, Reema; Menia, Nitin Kumar; Gupta, Vishali; Gupta, Amod
ABSTRACT: Optic disc neovascularization in uveitis is uncommon, and has been associated with chronic inflammations like Behcet's disease, Vogt-Koyanagi-Harada disease, sarcoidosis, etc. To our knowledge, optic disc neovascularization has not been reported in tubercular serpiginous-like choroiditis. We report three such cases.